Metallocorroles as Electrocatalysts for the Oxygen Reduction Reaction (ORR). Issue 9 (25th July 2016) - Mahammed, Atif; Gross, Zeev
Abstract: The oxygen reduction reaction (ORR) is the most important reaction in life processes and in energy transformation, such as fuel cells. Normally, the ORR in a fuel cell is very slow and a cathode ORR catalyst is needed to reach a practical usable level. Pt‐based materials are the most effective catalysts, but they are too expensive to make fuel cells commercially viable and hence extensive research has focused on developing alternative catalysts. First row transition metallocorroles are potent catalysts for many reactions, and they may eventually be used as true alternatives to the precious metals currently used. Regarding ORR, brominated cobalt corrole has been shown to operate almost as well as an industry standard platinum‐based catalyst. In this review, we would like to summarize the progress that has been made in this field. Abstract :